2008
DOI: 10.1007/bf03192552
|View full text |Cite
|
Sign up to set email alerts
|

Quality aware software product line engineering

Abstract: Meeting and managing quality requirements such as performance, security… in a reuse context (software product line…) has a problematic that it is not found in singlesystems. In this paper, an overview of aspects to consider is presented, including a review of existing approaches, as well as some conclusions, requirements and guidelines to address quality aspects in software product lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Previous studies found speed, security, ease of use, and integration in other systems as the main nonfunctional features of dashboards [79]. The ndings of the present study also indicated the importance of the mentioned features as non-functional requirements.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies found speed, security, ease of use, and integration in other systems as the main nonfunctional features of dashboards [79]. The ndings of the present study also indicated the importance of the mentioned features as non-functional requirements.…”
Section: Discussionsupporting
confidence: 76%
“…They distinguish between quality assessment applied in domain engineering and application engineering. Etxeberria et al [2008] presented a survey that additionally incorporates variability modeling, design, architecture, implementation, and testing. In contrast to both reviews, we focus only on product-line analysis that operate statically, our classification is more fine-grained, and we survey more approaches.…”
Section: Related Workmentioning
confidence: 99%
“…de Oliveira et al extend RiPLE-DE, a domain engineering process to create domainspecific software architectures for product lines to help realize quality attribute variability [5]. Etxeberria and Sagardui discuss quality-aware product line engineering [9], modeling of variation in quality attributes in product lines [8], the evaluation of quality attribute variability in product lines [6] and propose variabilitydriven quality evaluation of software product lines [7]. Niemela and Immonen explore capturing quality requirements of product family architectures [25].…”
Section: Quality Attributes In Product Linesmentioning
confidence: 99%